1988
DOI: 10.1210/endo-123-1-168
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Epidermal Growth Factor, Somatomedin-C/Insulin-Like Growth Factor I, and Transforming Growth Factor-β on Porcine Granulosa Cell Deoxyribonucleic Acid Synthesis and Cell Proliferation*

Abstract: Recent studies have suggested that the mammalian ovary synthesizes epidermal growth factor (EGF), somatomedin-C/insulin-like growth factor I (Sm-C), and transforming growth factor-beta (TGFb) and that these growth factors may in part form a basis for intraovarian regulation of granulosa cell proliferation and differentiation. The studies described herein were initiated to determine to what extent EGF, Sm-C, and TGFb function to regulate DNA synthesis and granulosa cell proliferation during primary monolayer cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
41
1
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(49 citation statements)
references
References 37 publications
5
41
1
1
Order By: Relevance
“…Most reports focused on granulosa cells, in which effects of TGFs on proliferation seemed to be species-dependent. TGF-(and/or EGF) stimulated proliferation in the majority of studied species including bovine, porcine, and human granulosa cells (Gospodarowicz & Bialecki 1979, May et al 1988, Skinner & Coffey 1988, but had no effect on rat cells (Bendell & Dorrington 1990). In contrast, TGFstimulated proliferation of rat granulosa cells (Dorrington et al 1988), but had no mitogenic activity of cells from cow or pig (May et al 1988, Skinner et al 1987.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most reports focused on granulosa cells, in which effects of TGFs on proliferation seemed to be species-dependent. TGF-(and/or EGF) stimulated proliferation in the majority of studied species including bovine, porcine, and human granulosa cells (Gospodarowicz & Bialecki 1979, May et al 1988, Skinner & Coffey 1988, but had no effect on rat cells (Bendell & Dorrington 1990). In contrast, TGFstimulated proliferation of rat granulosa cells (Dorrington et al 1988), but had no mitogenic activity of cells from cow or pig (May et al 1988, Skinner et al 1987.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-(and/or EGF) stimulated proliferation in the majority of studied species including bovine, porcine, and human granulosa cells (Gospodarowicz & Bialecki 1979, May et al 1988, Skinner & Coffey 1988, but had no effect on rat cells (Bendell & Dorrington 1990). In contrast, TGFstimulated proliferation of rat granulosa cells (Dorrington et al 1988), but had no mitogenic activity of cells from cow or pig (May et al 1988, Skinner et al 1987. In theca cells, TGF-/EGF stimulated proliferation in hen, cow and sheep (Roberts & Skinner 1991, Onagbesan et al 1994b, Campbell 1999, but had no effect on the cell number in rat (Foghi et al 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that EGF stimulates the proliferation of granulosa cells isolated from man [10], cattle [11,12] and pigs [10,13,14]. However, so far no reports have been found documenting the mitogenic effect of EGF in rat.…”
Section: Discussionmentioning
confidence: 98%
“…It is mitogenic for GCs in many large mammals (2,3) and promotes growth in long-term cultures of human GC-luteal cells (4). Although promoting GC division, TGF-a attenuates differentiated functions in these cells such as FSH-induced aromatase activity and E 2 synthesis (1,4).…”
mentioning
confidence: 99%